A new species of Tenagomysis (Crustacea: Mysida: Mysidae) from New Zealand with notes on three Tenagomysis species - Fukuoka, Kouki; Bruce, Niel L. (Zootaxa, 2005)
Tenagomysis longisquama sp. nov. is described from South Island, New Zealand. T. longisquama is readily distinguished from the other species of Tenagomysis by the elongate antennal scale with an acute apex and the 10to 16-subsegmented carpopropodus of the third to eighth thoracopodal endopods. T. macropsis Tattersall, 1923 and T. producta Tattersall, 1923, and an unidentifiable species, Tenagomysis sp., are also recorded from South Island. A key to the New Zealand species of Tenagomysis is provided.